Pre- and post-diagnostic β-blocker use and lung cancer survival: a population-based cohort study - Weberpals, Janick; Haefeli, Walter E.; Brenner, Hermann (Scientific reports, 2017)
Beta-blockers have been associated with decreased cancer mortality. However, evidence for lung cancer is sparse and reported beneficial effects might be based on biased analyses. In this so far largest study we investigated the association between β-blocker use and lung cancer survival. Therefore, patients with a lung cancer diagnosis between April 1998 and December 2011 were selected from a database linkage of the Netherlands Cancer Registry and the PHARMO Database Network. After matching eligible patients on the propensity score, adjusted hazard ratios (HRs) and corresponding 95% confidence intervals (CI) were calculated using Cox proportional hazards regression to investigate the association between pre-diagnostic and time-dependent β-blocker use and overall survival. Duration and dose-response analyses and stratified analyses by β-blocker type, histological subgroups and stage were conducted. Of 3,340 eligible lung cancer patients, 1437 (43%) took β-blockers four months prior to diagnosis. Pre-diagnostic β-blocker use was not associated with overall survival (HR 1.00 (0.92-1.08)) in the adjusted model. Time-dependent post-diagnostic analysis showed similar results with a HR of 1.03 (0.94-1.11). Trend analyses showed no association for cumulative dose (HR 0.99 (0.97-1.02)) and cumulative duration (HR 1.00 (0.96-1.05)). In conclusion, β-blocker use is not associated with reduced mortality among lung cancer patients.